Inside Youth Bases. Case of Selected bases in Zimbabwe (Global Journal of Human-Social Science, 2019)
The study explored the dynamics within political bases with a view to establishing interyouth relationships, inter-base dynamics and base-youth challenges. This was a qualitative study following an exploratory design. It employed the Social Modelling and Cognitive Theory which argues that youth learn aggression and belligerence from modelling behaviour. The study focused on selected five political bases in Harare and Mashonaland Central provinces which have all existed during the elections of 2002, 2008 and 2013 though the study focusses on 2008 and 2013 plebiscites. Data were collected through structured interviews with 25 youth aged between 17 and 35 years and complimented by archival records and previous studies. The analysis of data was done using Latent Content Analysis. The study established that there are several challenges associated with bases and that they have led to the creation of new cultures; violence, negative competition, substance abuse and a hardened generation.
Keywords: political bases; violent youth; political youth; youth violence